2016
DOI: 10.1002/anie.201603052
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine‐Based Selection of Drugs That Target Ion Channels from Combinatorial Venom Peptide Libraries

Abstract: Animal venoms represent a rich source of pharmacologically active peptides that interact with ion channels. However, a challenge to discovering drugs remains because of the slow pace at which venom peptides are discovered and refined. An efficient autocrine-based high-throughput selection system was developed to discover and refine venom peptides that target ion channels. The utility of this system was demonstrated by the discovery of novel Kv1.3 channel blockers from a natural venom peptide library that was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…The purification and characterization of individual components from whole venoms has traditionally been a rate-limiting step in the process of realizing the biomedical potential of venom components, and the additional constraint of low venom yields has limited the use of many taxa comprising smaller species. Zhang et al (2016) recently described a high-throughput screening procedure that involves construction of venom libraries starting only from a toxin-sequence database. Their approach was used, as a test case, to successfully identify toxins that would bind with high affinity to Kv1.3 channels.…”
Section: Introductionmentioning
confidence: 99%
“…The purification and characterization of individual components from whole venoms has traditionally been a rate-limiting step in the process of realizing the biomedical potential of venom components, and the additional constraint of low venom yields has limited the use of many taxa comprising smaller species. Zhang et al (2016) recently described a high-throughput screening procedure that involves construction of venom libraries starting only from a toxin-sequence database. Their approach was used, as a test case, to successfully identify toxins that would bind with high affinity to Kv1.3 channels.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the combination of high content peptide library with functional signal screen systems in intact mammalian cells would allow efficient panning of peptide library under physiological condition. Recently, Lerner and colleagues have developed a powerful autocrine-based signaling system which tethered peptide library to cell membrane and employed artificial signal transduction systems to observe peptide-transmembrane protein interaction (17)(18)(19)(20)(21)(22). Here, we provide a novel methodology for building high content peptide library in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lerner and colleagues have developed an autocrine-based signaling system in mammalian cell (17)(18)(19)(20)(21)(22). Through membrane-tethered peptide library and artificial signal transduction system, this new strategy could screen the agonist/antagonist peptides of GPCRs or ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…Discovery of ion channel blocking peptides in sea anemones [8,9] Synthesis and folding of ShK peptide [3] Isolation of ShK peptide from Stichodactyla helianthus [2] 3D solution structure of ShK [4] ShK shown to block K v 1.3 potassium channel in human T lymphocytes at pM concentrations [10] Binding surface of ShK on neuronal K v channels determined [34] Ionization and solution properties of ShK determined; importance of Asp 5 -Lys 30 interaction [13] ShK docked in K v 1. characterized [21] Conserved lysine-aromatic dyad shown to be conserved in sea anemone and scorpion K + channel-blocking peptides [11] ShK used to demonstrate structural conservation of K v 1.3 and K Ca 3.1 external vestibules [36] Role of disulfide bonds for K v 1.3 channel-blocking activity of ShK determined [14] Role of helical capping ST-motif class 4A for stabilizing first alpha helix in ShK determined [35] ShK and ShK-Dap 22 treat disease in rat model of multiple sclerosis [76] Mutation of pore-occluding Lys 22 in ShK alters binding in K v 1.3's external vestibule [35] Type III peptidomimetics of ShK developed with micromolar potency [15] ShK-F6CA, fluorophore-tagged ShK analog with selectivity for K v 1.3 over K v 1.1 developed and used to detect K v 1.3 on T cells by flow cytometry [40] ShK-Dap 22 less potent than ShK; less selective in equilibrium binding assays than patch clamp assays; high potency for Kv1.1-Kv1.2 heteromultimers [38] ShK-170 [ShK-L5] developed as specific inhibitor of K v 1.3 [5] ShK-186 [SL5] developed as specific inhibitor of K v 1.3; ShK-186 treats pristane-induced arthritis in rats and suppresses delayed type hypersensitivity response [6] ShK-186 paralyzes and prevents activation of effector memory T cells in a DTH response; ShK-186 treats chronic relapsing-remitting EAE in a rat model of MS [68] Durable pharmacological activity of ShK-186 in rats and non-human primates [41,42] Recombinant production of ShK in E. coli [16] ; ShK-Lys-amide specific K v 1.3 blocker developed [23] ShK-like domain in human MMP23 characterized and shown to block K v 1.3...…”
Section: Figure 1 | a Development Timelinementioning
confidence: 99%
“…[19][33] [34] By screening a combinatorial ShK peptide library, novel analogues were identified, which when fused to the C-termini of IgG1-Fc retained picomolar potency, effectively suppressed in vivo delayed type hypersensitivity and exhibited a prolonged circulating half-life. [35] Prolonged effects despite rapid plasma clearance: SPECT/CT imaging studies with a 111 In-DOTAconjugate of ShK-186 in rats and squirrel monkeys revealed a slow release from the injection site and blood levels above the channel blocking dose for 2 and 7 days, respectively. [28] Studies on human peripheral blood T cells showed that a brief exposure to ShK-186 was sufficient to suppress cytokine responses.…”
Section: Shk-dap 22mentioning
confidence: 99%